Competitiveness of the biomethane opposite with the CHP technology of biogas by definite plant size - Barta-Juhász, Ilona (Acta Agraria Debreceniensis, 2013)
The biogas sector has never before aroused so much attention as it does today. Combined heat and power (CHP) reliable and cost-effective technologies that are already making an important contribution to meeting global heat and electricity demand. Due to enhanced energy supply efficiency and utilisation of waste heat renewable energy resources, CHP, particularly together with district heating and cooling (DHC), is an important part of national and regional Green House Gas (GHG) emission reduction strategies.During my work I am going to use the basic data of a certain biogas plant than I assemble one model from that. Against the CHP technology I am going to plan a biogas cleaning-equipment. During my research it revealed, that in the case of a 1 MW output power plant it is not worthy to deal with biogas cleaning between national conditions. Investigating the quantity of heat recovery in the CHP technology it is obvious, that the net income at 1 m3 biogas is at least 72 times more than the cleaning technology (heat recovery is 0%).